Beschäftigungsmuster von Frauen und Männern: Auswertung des IAB-Betriebspanels 2012 - Sebastian Bechmann; Vera Dahms; Nikolai Tschersich; Marek Frei; Ute Leber; Barbara Schwengler (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
Seit vielen Jahren wird die Integration von Frauen auf dem Arbeitsmarkt, insbesondere die Gleichstellung von Frauen und Männern oder die Beteiligung von Frauen an der Betriebsführung rege diskutiert. Bereits 2008 wurden diese Themen mit den Daten des IAB-Betriebspanels aus betrieblicher Sicht beleuchtet. Der dies jährige Forschungsbericht versteht sich als eine aktualisierte Bestandsaufnahme. Die AutorInnen prüfen, ob und inwieweit sich in den vergangenen vier Jahren Veränderungen gezeigt haben: In welchen Betrieben arbeiten überdurchschnittlich häufig Frauen und in welchen Betrieben Männer? In welchen Punkten unterscheiden sich weibliche von männlichen Beschäftigungsverhältnissen? Inwiefern unterscheiden sich ausschließlich männergeführte Betriebe von ausschließlich frauengeführten Betrieben oder von Betrieben, die sowohl von Frauen als auch von Männern geführt werden? Gibt es Unterschiede in den betrieblichen Rahmenbedingungen zur Vereinbarkeit von Beruf und Familie, in der Förderung der Chancengleichheit von Frauen und Männern oder im Aus- und Weiterbildungsverhalten der Betriebe? – – For many years there have been lively debates about the integration of women in the labour market, especially in terms of equality between women and men or the integration of women in management positions. In 2008 the data from the IAB Establishment Panel (Fischer et al. 2009) shed light on the employment patterns of men and women from an establishments perspective. This years report therefore is an updated review that sets out to examine whether and to what extent there have been further changes in the last four years. The following questions are answered in detail: Which establishments employ higher than average numbers of women and which establishments men? And how have things developed over recent years? In how far does female and male employment differ? To what extent do establishments managed exclusively by men differ from those managed exclusively by women or establishments run by both women and men? Are there any differences between groups of establishments regarding the key conditions enabling family and working life to be reconciled and the promotion of equal opportunities for women and men? Are there differences in the way training and further education are handled in establishments run by men, women or a mixture of both? Women have benefited more than the average of all employees from the expansion of employment that began in 2005. Employment has expanded above all in service sector establishments which are dominated by women. Yet the difference in the volume of work put in by women or men - the so-called working hours gap - has declined only slightly. Taken against the background of the increased rate at which women participate in the labour force, this means that the increase in employment has largely been due to an increase in part-time jobs. The results of the IAB Establishment Panel show that in 2012 more than three quarters of part-time employees were women. Women are also increasingly active in jobs requiring a vocational qualification or university degree, yet they continue to a higher than average extent to pursue activities that do not require any training. In recent years there has been slight progress in terms of employing women in managerial functions. Compared to their proportion of the workforce they are still largely under-represented - particularly in top management level. This is the case in all sectors and in establishments of all sizes. In 2012 the management of establishments again continued to be a male domain. Nonetheless, over the last few years slight improvements have been apparent in the involvement of women in management functions. Large establishments in particular, but also medium-sized establishments, have made progress in including women in top level management, even though they are starting from a very low level. The inclusion of women in managerial responsibility has increased slightly overall. Only in large establishments equality-related activities form a part of everyday business life, but the great majority of medium-sized establishments are also active in the areas referred to. Public sector establishments offer measures from this spectrum of measures markedly more frequently than establishments in the private sector, and this is the case for establishments of all sizes studied.
Keywords: 330